การประเมินความสัมพันธ์ทางพันธุกรรมของพืชครามสกุล Indigofera ด้วยเทคนิคแฮตอาร์เอพีดี - บัวบาน, ศุภรัตน์; ธนานันต์, ธีระชัย; ธนานันต์, นฤมล (Thai Journal of Science and Technology, 2020)
Indigo plant (Indigofera L.) as a small shrub that has indican substance in trunks and leaves. Besides using as a herb, the indican can form natural dye through the process of soaking in the water. This research assessed the genetic relationship of 15 Indigofera samples using high annealing temperature random amplified polymorphic DNA (HAT-RAPD) technique. Seventy-two random primers were screened, and 12 primers could clearly increase the DNA amplification product. The total of 204 DNA bands appeared in sizes ranging from 320 to 3,000 base pairs, resulting in all polymorphism (100 %). In addition, a dendrogram using NTSYS-pc version 2.01e was constructed by unweighted pair group method with arithmetic mean (UPGMA). The coefficients of similarity were between 0.24-0.69, and could separate 15 Indigofera samples into 7 groups. The results of this research can be used to plan for further conservation and plant breeding.